Public Health Leadership in the Times of Covid-19: A Comparative Case Study of Three Countries - Villalobos-Dintrans, P (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The purpose is to understand the role of public leadership during the COVID-19 pandemic and advocate for a more active role of public health professionals in helping manage the crisis. Design/methodology/approach The authors use the framework developed by Boin et al. (2005) on crisis leadership. The authors focus on three of the core tasks - sense-making, decision-making and meaning-making - that are relevant to explain the role of public leaders during the ongoing crisis. The authors draw from the experience of three countries - Chile, France and the United States - to illustrate how these tasks were exercised with concrete examples. Findings Several examples of the way in which public leaders reacted to the crisis are found in the selected countries. Countries show different responses to the way they assessed and reacted to the COVID-19 as a crisis, the decisions taken to prevent infections and mitigate consequences, and the way they communicate information to the population. Practical implications A better understanding public leadership as a key for better crisis management, particularly for designing policy responses to public health crises. Public health leaders need to assume a more active role in the crisis management process, which also implies the emergence of a new class of public health leaders and a more prominent role for public health in the public eye. Originality/value The use of examples from three different countries, as well as the focus on the core leadership tasks during an ongoing crisis help not only assessing the crisis management but also extracting lessons for the coming months, as well as future public health emergencies. The three authors have a first-hand experience on the evolution of the crisis in their countries and the environment, since they are currently living and working in public health in Chile, France and the United States.